The Ability of Global Stock Exchange Mechanisms to Mitigate Home Bias: Evidence from Euronext - Pownall, Grace; Vulcheva, Maria; Wang, Xue (Management Science, 2014)
This paper examines the effects on equity home bias of two mechanisms adopted by Euronext when it was formed by the merger of four European countries' stock exchanges in 2002. The two structural mechanisms are the integration of trading platforms across the four predecessor exchanges and the creation of named segments of the integrated exchange on which firms could voluntarily list by precommitting to enhanced disclosure and transparency. Employing a difference-in-differences research design using other European Union companies as a control group, we document that the integration of the Euronext market was associated with a reduction in home bias for firms listed on the named segments of the Euronext exchange, but not for the nonsegment Euronext firms. Our results suggest that the reduction in transaction costs from the integration of the trading platforms did not make the nonsegment Euronext firms more attractive to the specific investors for whom the transaction costs were reduced. On the other hand, the decrease in information costs due to the precommitments to enhanced transparency made the segment firms more attractive to all categories of foreign investors, consistent with the information costs hypothesis. This paper was accepted by Mary Barth, accounting.